Clear cell carcinoma in the retromolar area: A case report. Issue 6 (November 2020) - Yasui, Yuta; Asoda, Seiji; Soma, Tomoya; Miyashita, Hidetaka; Hasegawa, Toshihiro; Ouchi, Takehito; Karube, Takeshi; Yasui, Takazumi; Onizawa, Katsuhiro; Nakagawa, Taneaki; Kawana, Hiromasa
Abstract: Clear cell carcinoma (CCC) is a malignant neoplasm of epithelial origin classified in the 2017 World Health Organization (WHO) classification as a low-grade salivary gland tumor consisting of glycogen-rich clear cytoplasm. We report a case of a 34-year-old woman presented in our department following the complaint of a mass in her right retromolar area. The tumor measured 10-mm in diameter and was elastic and hard mass. Spontaneous pain or tenderness and desensitization of the tongue were not observed. Marginal resection of the mandible was performed under general anesthesia. The lesion was located in the minor salivary gland that is mainly composed of mucus glands and had a relatively clearly defined circular shape. However, there was no film fabrication in the surrounding resions. Additionally, atypical cells comprising a clear cytoplasm and irregularly shaped pyknotic nuclei were growing in sheet form or island form, and markedly hyalinized fascicles were observed between the alveolar walls of the atypical cells. Immunohistochemical stains revealed these tumor cells to be positive for epithelial cell markers but negative for myoepithelial ones. Considering the above findings, the tumor was diagnosed as CCC. The patient is currently free from disease 37 months after surgery.